Existence and uniqueness of invariant measures of 3D stochastic MHD-α model driven by degenerate noise. Issue 2 (22nd January 2022) - Zhang, Rangrang
ABSTRACT: In this paper, we establish the existence and uniqueness of invariant measures of the 3D stochastic magnetohydrodynamic- α model (MHD- α ) driven by degenerate additive noise. We firstly study the Feller property of solutions and establish the existence of invariant measures by utilizing the classical Krylov–Bogoliubov theorem. Then, we prove the uniqueness of invariant measures for the corresponding transition semigroup by utilizing the notion of asymptotic strong Feller proposed by Hairer and Mattingly [Ergodicity of the 2D Navier–Stokes equations with degenerate stochastic forcing. Ann Math (2). 2006;164(3):993–1032]. The proof not only requires the investigation of degenerate noise, but also the study of highly nonlinear, unbounded drifts.